2014
DOI: 10.3390/molecules190914948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standardized Cranberry Extract on the Activity and Expression of Selected Biotransformation Enzymes in Rat Liver and Intestine

Abstract: Abstract:The use of dietary supplements containing cranberry extract is a common way to prevent urinary tract infections. As consumption of these supplements containing a mixture of concentrated anthocyanins and proanthocyanidins has increased, interest in their possible interactions with drug-metabolizing enzymes has grown. In this in vivo study, rats were treated with a standardized cranberry extract (CystiCran ® ) obtained from Vaccinium macrocarpon in two dosage schemes (14 days, 0.5 mg of proanthocyanidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Notably, orally ingested GFJ did not seem to affect hepatic CYP3A4 expression or activity, while decreasing small-intestinal CYP3A4 protein levels by >60% 64 . In contrast, the consumption of cranberry extract, which caused moderate increases in hepatic CYP3A and CYP1A1 activities, did not influence intestinal CYP1A1, CYP1A2, CYP2B and CYP3A expression in rats 65 . GFJ has been employed as a tool to modulate intestinal drug metabolism in numerous studies.…”
Section: Regulation Of Intestinal Cyp Expression and Functionmentioning
confidence: 68%
“…Notably, orally ingested GFJ did not seem to affect hepatic CYP3A4 expression or activity, while decreasing small-intestinal CYP3A4 protein levels by >60% 64 . In contrast, the consumption of cranberry extract, which caused moderate increases in hepatic CYP3A and CYP1A1 activities, did not influence intestinal CYP1A1, CYP1A2, CYP2B and CYP3A expression in rats 65 . GFJ has been employed as a tool to modulate intestinal drug metabolism in numerous studies.…”
Section: Regulation Of Intestinal Cyp Expression and Functionmentioning
confidence: 68%
“…PCs are highly efficient natural antioxidants, their antioxidant activity is 50 times higher than that of vitamin E and 20 times that of vitamin C, and their effects have been reported in a wide range of studies [12,27,43,44,45,46,47]. The results of the meta-analysis by Li et al [47] indicated that PCs could effectively improve the activity of anti-oxidative enzymes and reduce lipid peroxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism refers to the chemical structural transformation of drugs [439]. After entering the body, plant polyphenols are metabolized by various enzymes, such as cytochrome P450 [440] and catechol-O-methyltransferase (COMT) [441]. After oral administration of curcumin, its glucuronide conjugates or sulfate conjugates could be detected in the blood [442].…”
Section: Bioavailability Of Plant Polyphenolsmentioning
confidence: 99%